The Impact of the Ketogenic Diet on the Metabolic Profile, Hormonal Balance and Fertility in Women with PCOS: A Literature Review - Turemka, Mariola; Mandziuk, Aneta; Cygnarowicz, Aleksandra; Wojtas, Aneta Klaudia; Zabojska, Krystyna; Korotko, Urszula; Witowska, Kinga; Biskupski, Mikołaj; Hosseinnejad, Negar; Sacher, karolina (Quality in Sport, 2024)
Introduction: Polycystic ovary syndrome(PCOS) is the most common endocrine disorder among women of reproductive age. It is characterized by clinical symptom caused by high androgen level such as acne, hirsutism and irregular menstrual cycles. The cause of PCOS is unknown but both genetic and environmental factors are believed to play a role. The key elements in the patogenesis of this syndrome are insulin resistance, hyperinsulinemia and hyperandrogenism. PCOS increases the risk of metabolic and cardiovascular diseases. The aim of this review is to describe the efficiency, safety and potential benefits of the ketogenic diet on the metabolic profile, hormonal balance and fertility in women with PCOS. Materials and methods: A literature review was conducted using the databases such as Pubmed and Google Scholar. Results: The ketogenic diet focuses on reducing carbohydrate intake while proportionally increasing fat and protein consumption. This diet reduces insulin resistance and positively impacts Patients’ metabolic profile and hormonal balance. This contributes to improve fertility in women, who often experience difficulty conceiving. Conclusion: The results of the studies show that the ketogenic diet has a positive effect on metabolic profile and hormonal balance in Patients with PCOS. However, further research is needed in larger groups of Patients and over longer periods of time to evaluate whether it can become an effective form of therapy for PCOS Patients.